Psicoanálisis y tratamiento del autismo - Aguirre Cueva, María Eugenia (Machala: Universidad Técnica de Machala, 2022)
The present study raises the problem of the treatment of autism from psychoanalysis, to solve this problem it has been proposed to investigate what would be the treatment of autism from the psychoanalytic theory. It is a qualitative research where the technique of bibliographical review of books and scientific articles was used. The results of this study show that there are different psychoanalytic devices to intervene subjects with autism, for example, games, theraplay, among others. It can be concluded that psychoanalytic intervention helps subjects with autism to relate to the external world, and thus, they can establish communication with other individuals in the social environment and reinforce affective bonds.
El presente estudio plantea la problemática sobre el tratamiento del autismo desde el psicoanálisis, para resolver este problema se ha planteado indagar cuál sería el tratamiento del autismo desde la teoría psicoanalítica. Es una investigación cualitativa en donde se utilizó la técnica de revisión bibliográfica de libros y artículos científicos. Los resultados de este estudio, plantean que existen diferentes dispositivos psicoanalíticos para intervenir a los sujetos con autismo, por ejemplo, los juegos, theraplay, entre otros. Se puede concluir que la intervención psicoanalítica ayuda a los sujetos con autismo a relacionarse con el mundo externo, y así, puedan establecer comunicación con otros individuos del entorno social y reforzar vínculos afectivos.
Keywords: PSICOANALISIS; TRATAMIENTO; AUTISMO